UNIVERSITY EDUCATION OF SPECIALISTS IN INTERNATIONAL AFFAIRS AS A WAY OF PASSING CULTURAL CODE - I. M. Shepeleva (Vestnik MGIMO-Universiteta)
The article describes the cultural code approach to the process of higher education requires global understanding and awareness of the integrity of academic studies at the university, comprising both professional and humanitarian disciplines, such as philosophy, history, ethnography, psychology etc. International communication playing the key role in the development of the world community presupposes systemic and interdisciplinary approach to solving problems and facing challenges arising in the modern times. Language is the most essential component of communication whose organization is based on the principles of interaction, cooperation and politeness ensuring the molding of communicative norms of social behavior. Compliance with these norms creates conditions for effective exchange of opinions, shapes an environment for positive interaction and implementation of communicative strategies by participants in verbal disquisition. On the other hand, national pictures of the world, implanted in the conscience of a child by their family and society serve as natural limits to international communication and understanding cross-cultural peculiarities. They often prevent people from reaching rapport with their foreign counterparts, as their worldviews come into contradiction. National and cultural distinctions cause main differences between systems, norms and uses. National stereotypes, focusing on most typical features of a nation, could serve as a tool for overcoming this discrepancy. Holistic approach to studying a foreign language as an integral part of the culture, alongside with other humanitarian and social disciplines, involves a deep insight into core mental and spiritual values of the society. So, the guiding role of the university teacher consists in dealing with professional issues while addressing the wide cultural content and intercultural objectives.